2022
DOI: 10.1021/acs.chemmater.2c00989
|View full text |Cite
|
Sign up to set email alerts
|

Water Induced Structural Transformations in Flexible Two-Dimensional Layered Conductive Metal–Organic Frameworks

Abstract: Contents S1. Developing ab initio force fields Co 31 +0.761 Co 327 +0.672 Co 651 +0.713 Co 32 +0.733 Co 378 +0.725 Co 699 +0.786 Co 63 +0.761 Co 379 +0.769 Co 712 +0.681 Co 75 +0.729 Co 390 +0.670 Co 739 +0.692 Co 126 +0.735 Co 441 +0.683 Co 789 +0.661 Co 127 +0.715 Co 443 +0.727 Co 790 +0.743 Co 138 +0.793 Co 474 +0.675 Co 825 +0.811 Co 189 +0.776 Co 537 +0.701 Co 840 +0.715 Co 191 +0.690 Co 538 +0.710 Co 888 +0.704 Co 222 +0.728 Co 573 +0.717 Co 889 +0.725 Co 283 +0.735 Co 588 +0.773 Co 903 +0.678 Co 284 +0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Although some mechanism studies behind the different arrangements of the stacking modes in 2D MOFs have been reported, 37,38 the stacking mode characterization still solely relies on empirical results and measurements from experiments and cannot be reliably predicted prior to experimental synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some mechanism studies behind the different arrangements of the stacking modes in 2D MOFs have been reported, 37,38 the stacking mode characterization still solely relies on empirical results and measurements from experiments and cannot be reliably predicted prior to experimental synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although some mechanism studies behind the different arrangements of the stacking modes in 2D MOFs have been reported, , the stacking mode characterization still solely relies on empirical results and measurements from experiments and cannot be reliably predicted prior to experimental synthesis. Even though state-of-the-art analytical techniques such as powder X-ray diffraction (PXRD), single-crystal X-ray diffraction, extended X-ray absorption fine structure (EXAFS), high-resolution transmission electron microscopy, and K-edge X-ray absorption near edge structure can be used to characterize the stacking modes accurately, they are available only after the materials synthesis. , For this reason, the development of a reliable way to predict stacking mode is imperative to “screen” for materials with user-desired stacking modes in the 2D MOFs prior to the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamical feature implies the displacement of layers in 2D COF when water molecule is adsorbed, [17] which leads to a variation of π–π stacking distance. Reflex modules are applied to study the configurations (Figure 3b–c).…”
Section: Resultsmentioning
confidence: 99%
“…Since conventional FFs lack the parameters related to transition metals, several classes of FFs have been introduced for MOFs, including but not limited to universal force field for MOFs (UFF4MOFs), 65 MOF-FF, 66 Bristow-Tiana-Walsh (BTW) FF, 67 and ab initio parameterized FFs. 68,69 For the simulations presented here, we make use of a modified BTW FF where, for numerical stability, we replaced the original Buckingham potential for non-bonded interactions with a Lennard-Jones (LJ) potential. The details of derivation of this BTW-LJ FF are provided in Appendix D.…”
Section: Examples Of New Featuresmentioning
confidence: 99%